Arterial calcification in a rabbit - García-Romero, Carmen; Colombino, Elena; Oliver-Guimera, Arturo; Barragán, Agustín; Viana, David; Corpa, Juan Manuel; Ortega, Joaquín; Selva, Laura; Uzal, Francisco A.; Montero, Estefania (Brazilian Journal of Veterinary Pathology, 2025)
A 6.5-year-old spayed female domestic toy rabbit (Oryctolagus cuniculus) presented with a history of apathy, weight loss for approximately 2 weeks and paralysis of both hind limbs. Due to the worsening of its condition and poor prognosis, the rabbit was euthanized.